Digital-Based Online Presentation Media in Improving Students’ Language Skills - Kamaluddin, Kamaluddin; Azizah, Wardah; Allan, Meghy; Robert, Yoseef (Journal International of Lingua and Technology, 2022)
In this day and age, the need for technology is needed, especially in the world of education. Therefore, a variety of learning media are needed that help to develop education with the latest technology and are suitable for use in the learning process.  One of the learning media that helps in the learning process is digital-based online presentation media, such as power points. Digital-based online presentation media is a media that uses a network and is in digital form, which makes it easier for users in the learning process. The purpose of this study was to see whether this digital-based online presentation media could improve the language skills of students or not. This research is quantitative with a descriptive approach using survey methods using questionnaires or questionnaire research instruments. The results of this study show that this digital-based online presentation media can improve the language skills of grade 3 students of Madrasah Tsanawiyah Prof. Dr Hamka Maninjau. With the results of the research that has been carried out, it is known that digital-based online presentation media can be positively useful for improving the Arabic language skills of grade 3 students of Madrasah Tsanawiyah Prof. Dr Hamka Maninjau.